2013
DOI: 10.1177/0954405413502025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solid lubricants on wire and arc additive manufactured structures

Abstract: This paper reports a systematic study which examines the use of solid lubricants in the sequential deposition and machining of wire and arc additive manufactured parts and characterises the effects of solid lubricants on the microstrucure. This paper also describes the microstructure developed and the effect on micro hardness by manual cleaning of deposited layers with acetone. Mild steel wire consumable electrode G3Si1 with the diameter of 0.8mm was used. The use of graphite and molybdenum disulphide as solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The mechanical characteristics are almost similar for all the tests carried out and show that the anisotropy in both directions (layers stacking and deposition directions) is not relevant. The fracture strain e r is about 30% (also in accordance with the characteristics of the material according to AWS 18 ). For samples 3 and 6, the values of e r were not measured due to the loss of adhesion of the painting during the necking phase and, for this reason, the deformation e u was also reported at the maximum load recorded for all the tests.…”
Section: Tensile Tests and Full-field Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…The mechanical characteristics are almost similar for all the tests carried out and show that the anisotropy in both directions (layers stacking and deposition directions) is not relevant. The fracture strain e r is about 30% (also in accordance with the characteristics of the material according to AWS 18 ). For samples 3 and 6, the values of e r were not measured due to the loss of adhesion of the painting during the necking phase and, for this reason, the deformation e u was also reported at the maximum load recorded for all the tests.…”
Section: Tensile Tests and Full-field Analysissupporting
confidence: 76%
“…In order to achieve a suitable set-up for the tensile testing machine, the following mechanical properties of the as welded ER70S-6 were taken as reference values: 18,19 ultimate tensile strength 518-590 MPa; yield strength 424-490 MPa; elongation 27-30%.…”
Section: Methodsmentioning
confidence: 99%
“…Colegrove et al (2013) states that rolling enhances the grain refinement. Adebayo (2014) has studied the implication of solid lubricant application during the process. They concluded that also after cleaning the surface with Acetone, the traces of lubricant are still present and they affect the microstructure and hardness of the deposited material.…”
Section: "Wire+arc Additive Manufacturing" (Waam)mentioning
confidence: 99%
“…6 AM technology is characterized by its layer-by-layer manufacturing method, also widely known as 3D printing, providing metallic components with improved accuracy and surface finish with less set-ups. 7,8 AM fabrication methods are classified into a powder bed system, powder feed system, as well as a wire feed system. During the manufacturing process, AM components have a complicated thermal process, including direction heat extraction, repeated melting, and rapid solidification, leading to different mechanical properties from the conventional process.…”
Section: Introductionmentioning
confidence: 99%